The third transformation of Japan: An institutional narrative on agglomeration economies in abenomics - Nikander, Jarmo (My University, 2014)
Objective of the study The aim of this study is to understand the institutional implications in Abenomics in a spatial context, the contemporary economic reform taking place in Japan, which is to finally end over two decades of economic malaise. For theoretical perspective of choice, this study explores a synthesis of institutionalism as the main approach, complemented by economies of agglomeration in spatial economics, or New Economic Geography (NEG). The outcomes include a narrative with implications for future research, as well as possible future implications for the economy of Japan, itself. The narrative seeks to depict the dialogue between public discourse and governmental communication in order to create a picture of how this phenomenon is being socially constructed. This is done by studying the official communications by the Cabinet along with public media commentary on respective topics. The reform is studied with reference to historical socio-cultural, economic evolution of Japan, which in turn, is explored through a literature review. This is to assess the unique institutional characteristics of Japan pertinent to reform. Research method This is a social and exploratory qualitative study – an institutional narrative case study. The methodological approach was kept practical: in addition to literature review, a narrative, thematic content analysis with structural emphasis was used to construct the contemporary narrative based on the Cabinet communication. This was combined with practical analytic tools borrowed from critical discourse analysis, which were utilized to assess the implicit intertextual agenda within sources. Findings What appears to characterize the discourse is status quo bias that comes in multiple forms. The bias is also coded in the institutions surrounding the reform, wherein stakeholders have vested interests in protecting the current state of affairs. This correlates with uncertainty avoidance characteristic to Japan. Japan heeds the international criticism to deregulate on a rhetorical level, but consistent with history, the Cabinet solutions appear increasingly bureaucratic. Hence, the imposed western information-age paradigm of liberal cluster agglomeration seems ill-suited to Japan which lacks risk takers and a felicitous entrepreneur culture. The Japanese, however, possess vast innovative potential ascribed to some institutional practices and traits, but restrained by others. The derived conclusion is to study the successful intrapreneur cases in Japanese institutional setting as a potential benchmark for Japan specific cluster agglomeration, and a solution to its structural problems impeding growth.